Organizational skills of the enterprise – a process approach - Brzeziński, Marek (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The company’s organizational skills in resource-based theory play an increasingly important role both in the operational and strategic dimensions therein. The proposed map of processes shaping these abilities constitutes a substantive basis for the interdependence of resources and competences and the processes identified therein: reconfiguration, organizational, learning, routinization, as well as technological and organizational changes. During their implementation, the company’s organizational skills are being developed and upgraded; this process can be presented by means of one of the two logistic functions: with a continuous or step change process. The procedure of calculating the parameters of the function of increasing organizational skills has also been presented.